Multiple Bullous and Ulcers as Cutaneous Manifestations of Wegener’s Granulomatosis: A Rare Case Report - Pangastuti M; Rizqandaru T; Suwarsa O; Dharmadji HP; Sutedja E (Dove Medical Press, 2022)
Miranti Pangastuti, Trustia Rizqandaru, Oki Suwarsa, Hartati Purbo Dharmadji, Endang Sutedja Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Miranti Pangastuti, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +6281223114874, Email pangastuti.miranti@gmail.comAbstract: Bullous dermatoses is a heterogeneous group of blistering skin disorders that can either be inherited or acquired. Subepidermal blisters may result in ulceration and scarring following their rupture. Wegener's granulomatosis (WG) is a granulomatous necrotizing vasculitis affecting small- to medium-sized blood vessels. It is associated with anti-neutrophil cytoplasmic antibodies (ANCA) and can be manifested cutaneously as multiple bullous and ulcers. A case of WG was reported in an 18-year-old man presented with multiple skin bullous and ulcers. The patient was diagnosed with WG based on the findings from nasopharyngoscopy examination that revealed crusts in his nasal cavity; necrotizing granulomatous appearance on chest radiograph; hematuria on urinalysis; and positive ANCA blood test. This patient received a combination of methylprednisolone and methotrexate, resulting in improvement within four weeks of therapy. His multiple skin ulcers were treated with a combination of dialkyl carbamoyl chloride, hydrocolloid, and hydrogel dressings. This patient was in complete remission state after six months of treatment, which later followed by a relapse episode that occurred within one year. WG with multiple skin bullous and ulcers can mimic other diseases. Various examinations such as histopathology, direct immunofluorescence, and ANCA blood test may aid in determining the etiology of skin bullous and ulcers.Keywords: anti-neutrophil cytoplasmic antibodies, bullous, ulcers, Wegener's granulomatosis